A descriptive model of the current microelectromechanical systems (MEMS) development process - Sagoo, Jeevan; Tiwari, Ashutosh; Alcock, Jeffrey R. (Cranfield University, 2009)
This paper uses the IDEFØ process modelling technique to present an ‘As-Is' model for the current process of developing generic MEMS devices, this new model is based on information from current practitioners. The model shows a seven- stage process, from customer requirement specification to testing and verification, with multiple iterative loops between several stages of the model. Process-constraints on current MEMS development are also reported in the paper. A comparison was attempted between this As-Is model and the candidate models for future MEMS development available in literature. Differences include the number and placement of process iteration stages and the quantity and type of the development activities. Further comparison is difficult, partly because of the different approaches, taken to represent MEMS development stages and development flows, used by different autho